Islamic boarding school, the transformation of Islamic education institution and its strategic role in global era - Khamid, Abdul; Sutrisno, Sutrisno; Hariyadi, Rahmat; Zaman, Badrus (IAIN Salatiga, 2022)
Islamic boarding school (Pesantren) as the oldest education institution in Indonesia and as boarding based Islamic education, has strategic position in the society, especially for the students (santri), this position enables the Islamic boarding school to be effective medium to empower the society with any alteration and institution transformation which holds on to the underlying cultural values. The objectives of this research are to investigate the process of institution transformation, students’ revival, and Islamic boarding school strategic roles in global era by employing qualitative approach. The research findings indicate; First, Nuur El-Falah Foundation has transformed its institution from an orphanage for conflict victim children into Nuur El-Falah Agro Foundation which established Islamic Boarding School and formal education (Junior High School, Vocational High School, and Islamic Senior High School); Second, students’ revival are seen from its transformation from classic (salaf) students into modernization by going to formal education from Junior High School, Vocational High School, and Islamic Senior High School, even more students continue their study to public University and Islamic University; Third, Islamic boarding school administrators have strategic position in global era to be the front guard in escorting the students’ moral. The Islamic boarding school role as one of Indonesian students’ character builder should be preserved from year to year.